Аналіз можливостей юнацького спорту як соціальної системи у вихованні моральних якостей особистості - Тіняков, Артем Олександрович (НТУ "ХПI", 2010)
Work is devoted to the analysis of educator possibilities of youth sport as a difficult frame of society. The necessity of the use of rich potential of the system of youth sport is grounded for forming of morality of the young generation. Possibility and ways of the use of facilities is rotined, methods and organizational forms of sporting preparation of youths for education of moral qualities. The ways of forming components of moral qualities are certain.
Keywords: юнацький спорт; аналіз можливостей; колектив